A computational model for dynamics in effective usage of ICT public access centre - Ab. Aziz, Azizi; Yusop, Nor Iadah; Mat Aji, Zahurin; Ahmad, Faudziah (2013)
In Malaysia, ICTs have been identified as a crucial enabler in the knowledge-based economy to facilitate the acquisition, utilization, and dissemination of knowledge towards enhancing the economic and social values of society.Numerous programmes have been organized, developed, designed and executed to optimize the usage of these ICT Public access centres (telecentres).This paper will discuss important factors that contribute the effective usage of telecentres using a computational model.Simulation experiments for several cases pointed out that the model is able to reproduce interaction among selected scenarios in the literature.In addition, the model has been automatically verified against expected overall properties.